2014
DOI: 10.3389/fimmu.2014.00446
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antibodies: Clinical Significance, Mechanism of Interference with Immune Responses, and Possible Vaccination Strategies

Abstract: Neonates have an immature immune system, which cannot adequately protect against infectious diseases. Early in life, immune protection is accomplished by maternal antibodies transferred from mother to offspring. However, decaying maternal antibodies inhibit vaccination as is exemplified by the inhibition of seroconversion after measles vaccination. This phenomenon has been described in both human and veterinary medicine and is independent of the type of vaccine being used. This review will discuss the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
362
1
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(392 citation statements)
references
References 171 publications
(147 reference statements)
14
362
1
15
Order By: Relevance
“…Partial protection against the disease in these groups may be explained by the inhibitory effect of high maternal antibody titers on live vaccine at day old. Maternal antibodies suppress vaccine-induced immune responses (Niewiesk, 2014).…”
Section: Comparative Evaluation Of the Protective Efficacy Of Differementioning
confidence: 99%
“…Partial protection against the disease in these groups may be explained by the inhibitory effect of high maternal antibody titers on live vaccine at day old. Maternal antibodies suppress vaccine-induced immune responses (Niewiesk, 2014).…”
Section: Comparative Evaluation Of the Protective Efficacy Of Differementioning
confidence: 99%
“…Otro factor que puede influir en los resultados está relacionado con la variación inter-individual de la respuesta inmunológica, que a su vez puede estar influenciada por el genotipo de cada individuo e incluso por interferencias con los anticuerpos de origen materno (Niewiesk, 2014). También se han descrito interacciones hormonales tales como el efecto de feed-back negativo ejercido por otras hormonas tales como la testosterona o la inhibina sobre la liberación de FSH, sin embargo en el presente estudio esta situación es poco probable debido a que este hecho suele suceder en animales sexualmente maduros (Simoni et al, 1999).…”
Section: Discussionunclassified
“…Although much evidence has highlighted the benefits of maternal immunization, some studies have also shown a potential interference between maternally derived IgG antibodies and infant antibody responses [23]. Specifically, maternally derived IgG antibodies can inhibit immune responses against the same or related antigens after primary vaccination series in early infancy, a phenomenon termed "immunological blunting".…”
Section: The Effect Of Maternal Immunization In Infantsmentioning
confidence: 99%